Effects of Alfalfa Hay to Oat Hay Ratios on Chemical Composition, Fermentation Characteristics, and Fungal Communities during Aerobic Exposure of Fermented Total Mixed Ration - Mingjian Liu; Lin Sun; Zhijun Wang; Gentu Ge; Yushan Jia; Shuai Du (Fermentation, 2023)
The application of fermented total mixed ration (FTMR) is an effective method to prolong the use time of feed, but the understanding of the interaction mechanism between fungal microorganisms and silage quality and aerobic stability in FTMR is still limited. This study aimed to evaluate the effects of alfalfa (Medicago sativa L.) hay to oat (Avena sativa L.) hay ratios on chemical composition, fermentation characteristics, and fungal communities during aerobic exposure of fermented total mixed ration (FTMR). The supplement levels of oat were as follows: 200 g/kg oat hay (LO), 300 g/kg oat hay (MO), and 400 g/kg oat hay (HO). The water content of the three treatments was adjusted to 50% using a sprayer. After 60 days of ensiling, the bags were opened, and the chemical composition, fermentation characteristics, and fungal communities were measured after 3, 6, 9, and 12 days of aerobic exposure. The results suggested that the LO treatment significantly (p < 0.05) increased the aerobic stability than that in other treatments. The crude protein and lactic acid content in the three treatments were significantly decreased with the extension of the aerobic exposure period. Additionally, there was a remarkable (p < 0.05) higher lactic acid content observed in the LO treatment than that in the HO treatment during the aerobic stage. The PCoA showed that the compositions of the fungal community in the HO treatment were distinctly separated from the other two treatments. Compared with HO and LO treatments, the MO treatment observed relatively higher OTU, Shannon, and Chao1 indexes. Compared with LO and MO treatments, the abundances of the genes Saccharomyces and Wallemia were greater increased and decreased in the HO treatment, respectively. Integrated correlation analysis also underscores a possible link between the fermentation characteristics, aerobic stability, and significantly altered fungal community. This study suggested that the use of FTMR in production might prolong aerobic storage time when alfalfa was fermented in a mixture with ≤30% oat.